2016
DOI: 10.1002/adsc.201600299
|View full text |Cite
|
Sign up to set email alerts
|

Palladium on Carbon‐Catalyzed C−H Amination for Synthesis of Carbazoles and its Mechanistic Study

Abstract: 10% Palladium on carbon (10% Pd/C) successfully catalyzed the intramolecular C À Ha mination of various N-mesylated 2-aminobiphenyls in the presence of ac atalytic amount of pyridine Noxide in heated dimethyl sulfoxide (DMSO) under an oxygena tmosphere to afford the corresponding N-mesylcarbazoles.T he reactionw ould proceed via asingle-electron transfer process based on its significant suppression by the addition of as ingle-electron scavenger, tetracyanoquinodimethane (TCNQ), andt he substituents on the arom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 63 publications
0
16
0
Order By: Relevance
“…The synthetic methods of carbazoles via CÀH activation have also been reported. Carbazole skeletons could be constructed through CÀH amination, [6] CÀH arylation, [7] and coupling of two CÀH bonds. [8] Recently, we found that dibenzopalladacyclopentadienes obtained via CÀH activation of 2-iodobiphenyls exhibited novel reactivities.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The synthetic methods of carbazoles via CÀH activation have also been reported. Carbazole skeletons could be constructed through CÀH amination, [6] CÀH arylation, [7] and coupling of two CÀH bonds. [8] Recently, we found that dibenzopalladacyclopentadienes obtained via CÀH activation of 2-iodobiphenyls exhibited novel reactivities.…”
mentioning
confidence: 99%
“…Whereas replacing K 2 CO 3 with Li 2 CO 3 or Na 2 CO 3 resulted in lower yields (entries 2 and 3), the yield was improved to 53% by using Cs 2 CO 3 (entry 4). Solvent screening showed that the reactions almost failed to generate the desired product in other screened solvents except DMA, which gave the same yield as DMF (entries [5][6][7][8].…”
mentioning
confidence: 99%
“…Recently Sajiki's group reported the Pd/C‐catalyzed synthesis of N ‐mesylcarbazoles via intramolecular C–H amination of a variety of N ‐mesylated 2‐aminobiphenyls in the presence of a catalytic amount of pyridine N ‐oxide in heated DMSO under an O 2 atmosphere [Eq. (71)] …”
Section: Applications Of Pd/cmentioning
confidence: 99%
“…In addition, the maximum permissible amounts of residual metals, including Pd, in medicines are strictly defined by the International Conference on Harmonisation of Technical Requirements for Registration of Pharmaceuticals for Human Use (ICH) Q3D guidelines. , Therefore, the development of practical methods to reduce residual Pd in APIs or the reaction mixtures used in each synthetic step is strongly desired. Palladium on carbon (Pd/C), which is used as a heterogeneous catalyst for various reactions such as hydrogenations, C–H activation reactions, , and coupling reactions, can be easily removed from the reaction mixture, resulting in reduced Pd contamination in the crude reaction solution in comparison with the homogeneous Pd-catalyzed reaction . However, even a small amount of residual Pd in the product can sometimes exceed the ICH Q3D standard level and become a serious problem even for heterogeneous Pd-catalyzed reactions , because of the strong coordination ability of some functional groups for Pd species, such as aromatic rings and/or π-electron-rich unsaturated bonds within the substrates and/or products.…”
Section: Introductionmentioning
confidence: 99%